Evaluation of the Computer Fire Model DETACT-QS - Society for Fire Protection Engineers; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This engineering practice Guide, based on the DETACT-QS program, describes a model for predicting the response time of ceiling-mounted heat detectors/sprinklers and smoke detectors, installed under large unobstructed ceilings, for fires with user-defined, time-dependent heat release rate curves. The Guide provides information on the technical features, theoretical basis, assumptions, limitations, and sensitivities as well as guidance on the use of DETACT-QS. Evaluation is based on comparing predictions from DETACT-QS with results from full-scale fire experiments conducted in compartments with ceiling heights ranging from 2.44 m (8 ft) to 12.2 m (40 ft) and peak fire heat release rates ranging from 150 kW to 3.8 MW. Use of this model with building geometries or fire characteristics other than those used in this evaluation may require further evaluation or testing.
Introduction -- Model Description -- Scenarios for Which Evaluation Is Sought -- Theoretical Basis for the Model -- Mathematical and Numerical Robustness -- Model Sensitivity -- Model Inputs0 -- Model Evaluation -- Summary of Analysis0 -- Limitations/User Guidelines -- Appendix A -- Appendix B.
Keywords: Fire prevention; Buildings Protection.; Building information modeling; Computer simulation; Fire Science, Hazard Control, Building Safety; Building Information Modeling; Computer Modelling; Fire prevention -- Data processing; Fires -- Computer simulation